The girl from the Channel Islands [large type] - Lecoat, Jenny (Thorndike Press large print core, 2021)
After fleeing Vienna, Hedy Bercu, a Jewish woman living on the island of Jersey, is forced to hide in plain sight during the German occupation and to survive must depend on her own courage, her community, and a German soldier she befriends.